2013
DOI: 10.4103/0976-237x.111623
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of idiopathic gingival fibromatosis

Abstract: Idiopathic gingival fibromatosisis, a condition of undetermined cause can develop as an isolated disorder, but mostly it is associated with some syndrome. It usually begins at the time of eruption of permanent teeth but can develop with the eruption of deciduous dentition and rarely present at birth. This case report describes an unusual case of non-syndromic generalized idiopathic gingival fibromatosis in a 15-year-old male present since birth. Surgical treatment in the form of ledge and wedge procedure with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…Various modalities of treatment had been proposed including radical treatment with extraction of the involved teeth, which was reported not to favour a recurrence of the growth [6]. The treatment of choice in this condition was gingivactomy to satisfy the patient's aesthetics [7]. This was coincided with the current study in which gingivactomy was used for restoring the patient's happiness.…”
Section: Discussionsupporting
confidence: 53%
“…Various modalities of treatment had been proposed including radical treatment with extraction of the involved teeth, which was reported not to favour a recurrence of the growth [6]. The treatment of choice in this condition was gingivactomy to satisfy the patient's aesthetics [7]. This was coincided with the current study in which gingivactomy was used for restoring the patient's happiness.…”
Section: Discussionsupporting
confidence: 53%
“…8 The purpose of the treatment should include measures to correct mastication and phonation, promoting healthy growth and development, and, if possible, reduce emotional impacts due to aesthetic improvement. 34…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20]27 The syndromes associated with gingival fibromatosis include Zimmerman -Laband syndrome (GF, hypoplastic distal phalanges, hepatosplenomegaly, epilepsy, hypertrichosis, and mental retardation), Jones syndrome (GF and progressive neural deafness), Klippel -Trenaunay syndrome (GF, hemihypertrophy, Nevus flammeus, hemangioma, hypertlorism, and macrocephaly), Ramon syndrome (GF, hypertrichosis, mental retardation, epilepsy, rheumatoid arthritis, and diabetes mellitus), Rutherfurd syndrome (GF, unerupted teeth, corneal dystrophy, and mental retardation), Cross syndrome (GF, nanophthalmos, microcornea, and severe mental retardation), Murray -Puretic Drescher syndrome (Juvenile hyaline fibromas), Cornelia de Lange Syndrome, and Tuberous sclerosis. 4,[18][19][20][21]27 In the current study no patient presented with generalized gingival enlargement associated with any syndrome. It has recently been found that there are qualitative and quantitative differences in transforming growth factor beta -isoform (TGF-β) and receptor expression by fibroblasts in gingival overgrowth and this may contribute to the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The patients often used to chew food with their gums and rarely used to practice oral hygiene measures. [20][21][22][23] Various procedures available for excision of gingival enlargement include external or internal bevel gingivectomy with gingivoplasty using scalpel, electrosurgery and laser surgery. 20 There is no consensus among authors regarding the exact time when surgery should be accomplished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation